English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

any help is appreciated :)

2006-11-15 11:08:46 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

Start with your equation:
x² - 8x - 19 = 0

Move the unit term to the right side:
x² - 8x = 19

To complete the square, take half the coefficient on the x-term (-4) and square it (16). Add this to both sides:
x² - 8x + 16 = 19 + 16

Now you can rewrite the left side as a perfect square:
(x - 4)² = 35

Take the square root of both sides:
x - 4 = +/-sqrt(35)

So you have two answers:
x - 4 = sqrt(35)
or
x - 4 = -sqrt(35)

Add 4 to both sides:
x = 4 + sqrt(35)
or
x = 4 - sqrt(35)

2006-11-15 11:11:07 · answer #1 · answered by Puzzling 7 · 1 0

x^2 - 8x = 19
divide 8 by 2 and square that answer
(8/2)^2 = 16
x^2 - 8x + 16 = 19 + 16
(x + 4)^2 = 25

2006-11-15 19:13:31 · answer #2 · answered by trackstarr59 3 · 0 0

x² - 8x - 19 = 0
x² - 8x = 19
x² - 8x + 16 = 19 + 16 ........(16 is 8/2 squared)
(x - 4)² = 35
x - 4 = ±√35
x = 4 ± √35

2006-11-15 19:12:14 · answer #3 · answered by Philo 7 · 1 1

fedest.com, questions and answers